Fenomena implementasi pembelajaran daring selama wabah covid-19 di SD Negeri Degan Kabupaten Pati - Niken Larasati; Sandra Bayu Kurniawan; Peduk Rintayati (Jurnal Pendidikan Dasar, 2021)
This research aims to describe the meaning of online learning implementation during the Covid-19 pandemic at Degan State Elementary School, Pati regency. This research is a qualitative study using a phenomenological research design. The sampling technique used was the purposive sampling technique. The technique of collecting data used interview, observation, and documentation. The data validity test used technical triangulation. Data analysis is obtained from results of data collection using interactive analysis which includes data collection, data reduction, data presentation, and concluding. The results showed that implementation of online learning in Degan State Elementary School started with teacher preparation including making a porta, promissory note, syllabus, and lesson plan. The learning process was done through the WhatsApp group. The learning process started with greetings, motivation, perception, presenting material through learning videos, messages or voice messages, questions and answers, and submitting assignments. The assessment process is carried out using two methods, the first method is students sending their assignments by WhatsApp and the other method is students coming to school to directly collect assignments once a week. Obstacles in the implementation of online learning are network, internet quota, cellphone, and discipline.